PERINATAL OUTCOME OF MECONIUM STAINED AMNIOTIC FLUID - Dr Purva Mahapatra; Dr Subhalaxmi Dash; Dr Satyajit Jena; Dr Sudhanshu Sekhara Nanda; Dr Chintamani Mahanta (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Objective To determine the perinatal outcome of labouring mothers with meconium-stained amniotic fluid (MSAF).Methods A prospective observational  study was conducted among labouring mothers with meconiumstained amniotic fluid from  December  2019 to june 2020 at SCB Medical College ,Cuttack, Odisha, India . Data was collected with pretested structured questionnaires. A Chi-square test used to check statistical associations between variables. Those variables with a p-value of less than 0.05 were selected for cross-tabulation and binary logistic regression. P-value set at 0.05, and 95% CI was used to determine the significance of the association. Relative risk was used to determine the strength and direction of the association.Result Among 556 participants, there where 278(50%) primigravida in a stained fluid group. Labour was induced in 145 (26.07%) of the stained fluid group and has a statistically significant association with meconium staining. The stained fluid group was twice more likely to undergo operative delivery compared with a non-stained fluid group. There were more low Apgar scores at birth (36.8% ), birth asphyxias (9% ), neonatal sepsis (1% ), neonatal death (1%), and increased admissions to neonatal intensive care unit among the meconium-stained group. Meconium aspiration syndrome was seen in 35(6.2%) of the stained fluid group.Conclusion Meconium-stained amniotic fluid is associated with increased frequency of operative delivery, birth asphyxia, neonatal sepsis, and neonatal intensive care unit admissions compared to clear amniotic fluid.